BONE MINERAL DENSITY IN FEMALE MEDICAL STUDENTS RESIDING IN HOSTEL, A SINGLE-CENTER STUDY - Humayun Suqrat Hasan Imam; Uzma Sagheer; Tahir Ismail; Muhammad Khalid Saddiqui (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Osteopenia is a condition in which bone mineral density (BMD) is decreased. If not timely prevented, it can be aggravated to severe osteoporosis and a risk for fractures. Our objective was to find out the frequency of osteopenia and osteoporosis in female medical students residing in hostel of Punjab Medical College Faisalabad. METHODOLOGY: A Cross-sectional study was conducted in Liaqat and Fatima hall of Punjab Medical College Hostel, Faisalabad from 1st June 2014 to 31st August 2014 after ethical review committee approval. By using non probability convenient sampling technique, 212 female students of MBBS residing in Punjab Medical College Hostel were included in study. Predesigned questionnaire was used to collect data. Data was analyzed by using 17 version of SPSS. RESULTS: Out of 212 females, the age of 70 (33%) females was <20 years, the age of 80 (38%) females was 21-22 years and 62 (29%) females was ≥ 23 years. The frequency of osteoporosis was 81(38%), osteopenia was 123 (58%) and normal females were only 8 (4%). In relation to regular exercise, significant association was observed with p <0.001. CONCLUSION: Frequency of osteopenia and osteoporosis was high among female medical students. To address this serious public health issues, health education should be provided.